Long Noncoding RNA and Circular RNA Expression Profiles of Monocyte-Derived Dendritic Cells in Autoimmune Hepatitis - Yang, Fan; Fan, Xiaoli; Liu, Yifeng; Shen, Yi; Zhao, Shenglan; Zheng, Yanyi; Men, Ruoting; Xie, Yan; Yang, Li (Frontiers in Pharmacology, 2021)
Autoimmune hepatitis (AIH) is a chronic liver disease caused by disruption of liver immune homeostasis. The effect of dendritic cells (DCs) on the pathogenesis of AIH is not fully understood. Long noncoding RNAs (lncRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs) have been shown to play critical roles in the regulation of cell function. In this study, we analyzed the immunophenotypic characteristics of DCs in the peripheral blood. The percentage of mature DCs was higher in AIH patients than in healthy controls (HCs), and the proportion of mature DCs decreased after treatment. We isolated monocyte-derived DCs (moDCs) from the peripheral blood, obtained whole RNA-sequencing (RNA-seq) data for the moDCs from the two groups, and identified differentially expressed (DE) lncRNAs, circRNAs, miRNAs and mRNAs. In addition, we performed Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses for the DE mRNAs and constructed competing endogenous RNA (ceRNA) networks. ENST00000543334, hsa_circ_0000279, and hsa_circ_0005076 were selected and validated by RT-qPCR. These results provide a possible molecular mechanism of DCs in the pathogenesis of AIH and identify some potential therapeutic targets.